Sex differences in the relationship between socioeconomic status and cardiovascular disease: A systematic review and meta-analysis - Backholer, K.; Peters, S.; Bots, S.; Peeters, A.; Huxley, Rachel; Woodward, M. (BMJ Publishing, 2016)
Background: Low socioeconomic status (SES) is a known risk factor for cardiovascular disease (CVD) but whether its effects are comparable in women and men is unknown. Methods: PubMed MEDLINE was systematically searched. Studies that reported sex-specific estimates, and associated variability, of the relative risk (RR) for coronary heart disease (CHD), stroke or CVD according to a marker of SES (education, occupation, income or area of residence), for women and men were included. RRs were combined with those derived from cohort studies using individual participant data. Data were pooled using random effects meta-analyses with inverse variance weighting. Estimates of the ratio of the RRs (RRR), comparing women with men, were computed. Results: Data from 116 cohorts, over 22 million individuals, and over 1 million CVD events, suggest that lower SES is associated with increased risk of CHD, stroke and CVD in women and men. For CHD, there was a significantly greater excess risk associated with lower educational attainment in women compared with men; comparing lowest with highest levels, the age-adjusted RRR was 1.24 (95% CI 1.09 to 1.41) and the multiple-adjusted RRR was 1.34 (1.09 to 1.63). For stroke, the age-adjusted RRR was 0.93 (0.72 to 1.18), and the multiple-adjusted was RRR 0.79 (0.53 to 1.19). Corresponding results for CVD were 1.18 (1.03 to 1.36), 1.23 (1.03 to 1.48), respectively. Similar results were observed for other markers of SES for all three outcomes. Conclusions: Reduction of socioeconomic inequalities in CHD and CVD outcomes might require different approaches for men and women.